BARROS, D. L. P. DE (ORG.) OS DISCURSOS DO DESCOBRIMENTO: 500 E MAIS ANOS DE DISCURSOS. SÃO PAULO: EDUSP; FAPESP, 2000, 270 PÁGS. - Ottoni, Maria Aparecida R.; Lima, Maria Cecília de (Cadernos de Linguagem e Sociedade, 2010)
BARROS, D. L. P. DE (ORG.) OS DISCURSOS DO DESCOBRIMENTO: 500 E MAIS ANOS DE DISCURSOS. SÃO PAULO: EDUSP; FAPESP, 2000, 270 PÁGS.